Particulate matter exposure in major manufacturing industrial zones of Nigeria: Non-carcinogenic human health risk assessments, spatiotemporal analysis and dispersion modeling - M.A. Lala; A.L. Vincent; O.A. Adesina; L.T. Popoola; O.J. Odejobi; J.A. Sonibare (Case Studies in Chemical and Environmental Engineering)
The increasing rate of industrialization and urbanization in Nigeria has been identified as a significant contributing factor to particulate matter (PM) pollution. Anthropogenic PM emissions from manufacturing industries and other related urbanization activities across the country are of great concern. This study therefore focused on monitoring PM2.5 and PM10 levels over selected areas within the 4 major manufacturing industrial zones of Nigeria. The study simulated the trajectory and dispersion patterns of the more harmful particulate matter and also assessed the non-carcinogenic human health risks of the monitored PM. Air Matters smart application, a satellite-based sensor was used to quantify PM2.5 and PM10 hourly for 61 environmental dreadful harmattan days (28th November 2023 to 28th January 2024). Hybrid single-particle Lagrangian integrated trajectory (HYSPLIT) model was used to predict the trajectory and dispersion patterns of PM2.5 over the studied areas. The risk assessments were estimated via pollutant standards index (PSI), toxicity potential (TP), and hazard quotient (HQ); using the year 2021 updated World Health Organization (WHO) guideline for PM2.5 and PM10 as the reference exposure limit. The results showed that the ambient PM2.5 (daily average) over the 4 selected areas were above the WHO standards (15 μg/m3). For PM10, only the north-central industrial zone is significantly greater than the updated WHO standards (45 μg/m3). The HYSPLIT models revealed that it would take a longer period for the released particles to be fully dispersed. The dispersion patterns are closer to the lower layers of the atmosphere and this implies a possibility of risk for the exposed vulnerable populations. Investigation of the risk assessments showed that exposure to PM in all 4 major manufacturing industrial zones of Nigeria is likely to pose a negative impact on human health, particularly on the most susceptible groups. Thus, more stringent measures should be put in place by the government and all stakeholders to ensure better air quality in Nigeria.